Influence of partial or total substitution of wheat flour and sunflower oil with Sacha inchi (Plukenetia volubilis L.) flour and oil on the quality and nutritional properties of cookies - Fernando E. Alejandro Ruiz; Julio F. Ortega Jácome; Margarita G. Chancay Pinargote; José R. Mora; Andrea C. Landázuri; Paola Vásconez Duchicela; Julio Vásconez Espinoza; Pablo Beltrán-Ayala; María J. Andrade-Cuvi; José M. Álvarez-Suárez (PLoS ONE, 2026)
Background The increasing demand for healthier and more sustainable foods has driven the reformulation of bakery products using alternative ingredients. Sacha inchi ( Plukenetia volubilis L.), an Amazonian oilseed rich in proteins, unsaturated fatty acids, and bioactive compounds, represents a promising resource to enhance the nutritional and functional quality of baked goods while valorizing agro-industrial by-products. Methodology This study investigated the effects of partially or totally replacing wheat flour and sunflower oil with defatted Sacha inchi oilcake flour and Sacha inchi oil on the nutritional, physicochemical, and functional properties of cookies. Nine formulations were developed, including a control and eight experimental variants. Proximate composition, mineral content, lipid profile, total polyphenols, antioxidant activity (FRAP and DPPH assays), texture, geometry, and color parameters were evaluated. Results Cookies containing Sacha inchi flour showed significant increases in protein (up to 19.65%), fat, fiber (6-fold higher), ash, and energy, with a reduction in carbohydrates. Mineral content increased markedly for calcium (10.8-fold), magnesium (10.2-fold), potassium (3-fold), phosphorus (5.4-fold), and zinc (4.6-fold), while iron decreased by 25%. Lipid profiling revealed a higher proportion of polyunsaturated fatty acids, particularly α-linolenic acid (omega-3), and lower saturated fats in cookies containing Sacha inchi oil. The incorporation of Sacha inchi ingredients also increased total polyphenols (up to 1.46-fold) and antioxidant activity (up to 1.99-fold). Texture analysis showed that Sacha inchi flour reduced hardness (up to 5.8 times softer than control), whereas Sacha inchi oil increased firmness (up to 2.4 times). Full replacement of sunflower oil increased cookie diameter and spread ratio, while Sacha inchi flour reduced diameter and increased thickness. Color parameters were also affected, reflecting compositional and Maillard-related changes during baking. Conclusions Replacing wheat flour and sunflower oil with Sacha inchi flour and oil enhanced the nutritional profile, fatty acid composition, and antioxidant capacity of cookies, while modulating their texture and geometry. These findings demonstrate the technological feasibility of using Sacha inchi derivatives as functional ingredients in bakery products, supporting the development of sustainable, health-oriented foods and promoting the valorization of Amazonian crops and by-products.